2016
DOI: 10.1016/j.fluid.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

On the prediction of critical temperatures of ionic liquids: Model development and evaluation

Abstract: In this study, the Guggenheim equation was used to estimate the critical temperature (T c) of 106 ionic liquids using experimental surface tension data as inputs. A group contribution (GC) and a Quantitative Structure−Property Relationship (QSPR) model were also developed to correlate/predict the T c of ionic liquids. It was shown that a lack of sufficiently large database for T c lead to the development of models with low prediction capability. The model's output as well as the T c values estimated from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
0
11
1
Order By: Relevance
“…In this respect, it should be emphasized that the predictions of both models may not reflect their possible true values. As indicated by Sattari et al, the current methods cannot evaluate these data in a reliable manner. Table S1 of the Supporting Information shows that the T c and P c values of the considered ILs estimated thus far by various methods exhibit a particularly large divergence.…”
Section: Resultsmentioning
confidence: 95%
“…In this respect, it should be emphasized that the predictions of both models may not reflect their possible true values. As indicated by Sattari et al, the current methods cannot evaluate these data in a reliable manner. Table S1 of the Supporting Information shows that the T c and P c values of the considered ILs estimated thus far by various methods exhibit a particularly large divergence.…”
Section: Resultsmentioning
confidence: 95%
“…In such cases, reliable methods to indirectly deduce the critical constants from experimental data measured at lower temperatures would be quite welcome considering the importance of these properties in a large variety of thermodynamic models. Following this line of thought, it has been suggested that one could take advantage of the fact that the surface tension vanishes at T c , to estimate its value from experimental surface tension data 7,45‐48 …”
Section: Methodsmentioning
confidence: 99%
“…The prevailing approaches used for the prediction of critical properties are centered around the group contribution (GC) concept, 1,5 although more computationally intensive methods such as the quantitative structure–property relationship (QSPR) methodology, 6‐9 as well as molecular simulations 10 have also been employed for this purpose. Additionally, numerous studies have made use of two macroscopic properties representing molecular energy and molecular size, in contrast to the QSPR methods where molecular descriptors are utilized, to predict the critical properties with particular focus on homologous series of hydrocarbons and hence with limited generalizability 8,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative structure property relationship (QSPR) was also an effective approach for prediction of T c . It mainly explores quantitative relations between molecular structure and physicochemical properties of compound accurately using statistic and theoretical calculation.…”
Section: Introductionmentioning
confidence: 99%
“…These models can predict the properties of unknown compound quickly and help to understand theoretically the differences of substances on the basis of molecular structure, providing guidance for high efficiency synthesizing compounds experimentally. Yao, Godavarthy, Sola, and Kazakov proposed their QSPR models to predict critical parameters of pure substances, and Ramjugernath developed a QSPR model to correlate/predict the T c of ionic liquids. These QSPR models all occupied preferable prediction and enough precision.…”
Section: Introductionmentioning
confidence: 99%